Video evidence of January 6 Capitol attack missing from US government website - Betts, Anna (The Guardian, 2025)
Attorneys representing a collection of news organizations said in a legal filing submitted on Tuesday that video evidence used during the sentencing of a rioter involved in the 6 January 2021 attack on the US Capitol had vanished from an online government platform.
United States of America
Keywords: Law (US); Trump administration; US Capitol attack; US crime; US news; US politics